2005
DOI: 10.1111/j.1570-7458.2005.00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to the rice leaf bug, Trigonotylus caelestialium, is conferred by Neotyphodium endophyte infection of perennial ryegrass, Lolium perenne

Abstract: Neotyphodium fungal endophytes form mutualistic symbiotic associations with many grasses of the subfamily Pooideae, including important forage and turfgrass species. This relationship provides a competitive advantage to the host plant by increasing abiotic/biotic stress tolerance, such as its resistance to drought, diseases, and insect pests. The insect deterrent effects of endophytes are now receiving attention in Japan, as insect pests growing in meadows are causing problems in adjacent rice paddies. One of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
(14 reference statements)
3
20
0
Order By: Relevance
“…It is possible that chemicals toxic to O. furnacalis and S. inferens are present in N. lolii infected L. perene, but the effect observed in the trial can be attributed entirely to feeding deterrence. Enhanced resistance to those insects observed in this study was similar to the data reported from the same plant with other insects species (Koga et al, 1997;Shiba and Sugawara, 2005). This indicates that L. perenne with N. lolii may have strong feeding deterrent ability that results in the starvation of a broad spectrum of insects.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It is possible that chemicals toxic to O. furnacalis and S. inferens are present in N. lolii infected L. perene, but the effect observed in the trial can be attributed entirely to feeding deterrence. Enhanced resistance to those insects observed in this study was similar to the data reported from the same plant with other insects species (Koga et al, 1997;Shiba and Sugawara, 2005). This indicates that L. perenne with N. lolii may have strong feeding deterrent ability that results in the starvation of a broad spectrum of insects.…”
Section: Discussionsupporting
confidence: 80%
“…lolii-infected L. perenne used in this study (KE+1996-7) are known to have marked levels of resistance to the bluegrass webworm, Parapediasia teterrella (Zincken) and T. caelestialium (Koga et al, 1997;Shiba and Sugawara, 2005). The experiments in our current study indicate that this plant also has excellent resistance to O. furnacalis and S. inferens and it means that the prevention of feeding damage by these insects on L. perenne plants is possible with the endophyte.…”
Section: Discussionmentioning
confidence: 99%
“…A predictive model for plant damage by this Lepidoptera has been built considering the temperature effect on alkaloid levels and their action on insect development [158]. L. perenne infected with Neotyphodium spp shows deterrency to Trygonotylus caelestialium Kirkaldy (Heteroptera: Miridae) due to the presence of peramine (45) [159]. L. perenne pasture infected by Acremonium lolii in New Zealand is more resistant to the curculionid Listronotus bonariensi Kuschel than the endophyte-free plants.…”
Section: Tomatinementioning
confidence: 99%
“…Because this method is remarkably useful for maintaining stock cultures, researchers have subsequently carried out many studies on the biology of T. caelestialium using this rearing method (Mima et al, 2002;Takita, 2002;Higuchi and Takahashi, 2003Goto and Higuchi, 2004;Ishimoto, 2004bIshimoto, , 2007Ito, 2004Ito, , 2007Kakizaki, 2004;Kobayashi and Kikuchi, 2004;Shiba and Sugawara, 2005;Ishimoto and Sato, 2006;Fukuyama et al, 2007;Higuchi et al, 2007;Niiyama et al, 2007). However, if the nymphs of T. caelestialium were to hatch simultaneously from eggs laid by females on consecutive days, the experiments on this insect would certainly become more efficient since many same-day-old bugs could be obtained synchronously on the same day.…”
Section: Introductionmentioning
confidence: 99%